THE STATUS OF THE FAMILY MAGNOLIACEAE IN THE BAVI NATIONAL PARK - Quang Nam, Vu; Ha Chi, Nguyen; Van Ha, Dang (Journal of Forestry Science and Technology, 2019)
The family Magnoliaceae is one of the important groups in flowering plants and the important component of tropical rain forest. With ca. 300 Magnolias species world-wide, there are at least 60 species occurring in Vietnam, distributed throughout the country. To provide more knowledges on the family Magnoliaceae in defined forests, we select a study on the status of the family Magnoliaceae in Bavi National Park. The field trips were carried out to collect the specimens and other related information such as morphological and ecological characters, distribution, etc. These specimens were compared with the types and other realated species for identification. The compared morphology was the method used for plant taxonomy. The results show that there are seven species, belonging to three genera of the family Magnoliaceae are occuring in this site. They are Michelia alba, M. tonkinensis, M. foveolata, M. balansae, Magnolia aff. fistulosa, Manglietia phuthoensis, and M. conifera, three of which are cultivated as Michelia alba, M. tonkinensis and Manglietia phuthoensis. In each species, information of taxonomic treatment, vernacular name, morphological character, basic distribution and ecology, and note are provided. In addition, typus specimens and photos of these species as well as the key to genus and species are also given. This will be very useful for identification and a exact evidence for other sciences as species conservasion, biology, forestry, etc. in Bavi National Park.